Numerical analysis of fracturing behavior in fully-graded concrete with oversized aggregates from mesoscopic perspective. (30th August 2020) - Qin, Xiangnan; Gu, Chongshi; Shao, Chenfei; Fu, Xiao; Vallejo, Luis; Chen, Yue
Highlights: An approach to establish two kinds of mesoscale models synchronously for fully-graded concrete is presented. The main cracking mode of mixed-mode fracturing in fully-graded concrete is visualized. Batch embedding technique of cohesive elements is illustrated and developed by a Python script. Uniaxial compressive and tensile experiments are conducted with 2D and 3D meso-structures of fully-graded concrete. Abstract: Complicated fracture modes of fully-graded concrete are investigated at mesoscale with the proposed numerical method in this study. A generation method for two kinds of meso-structures, which gets the randomness of the appearance and distribution of aggregates involved, is proposed based on the mesoscopic features of fully-graded concrete. Cohesive elements are globally inserted to the mesoscale models to capture the fracture propagation with batch embedding technique, and the description and visualization of main cracking mode of fractures are realized based on relative energy proportions. Uniaxial compressive and tensile experiments are conducted with 2D and 3D models to validate the proposed method for simulating fracturing behavior, and the numerical outputs show high consistency with the experimental results and demonstrate that the proposed method is feasible to characterize the fracturing features of fully-graded concrete at mesoscale eventually.